Successful treatment of a patient with herbal drug-induced immune thrombocytopenic purpura using freshly donated blood - Nwagu, Marcellinus Uchechukwu (Universa Medicina, 2018)
BackgroundDrug-induced thrombocytopenia (DITP), which also includes thrombocytopenia induced by beverages, foods, and herbal remedies, is an important clinical problem for haematologists. Drug-induced thrombocytopenia is often misdiagnosed as immune thrombocytopenic purpura with resulting inappropriate treatment. Immune thrombocytopenic purpura (ITP) is a clinical disorder that leads to easy bruising (purpura), excessive bleeding or extravasation of blood from capillaries into skin and mucous membranes (petechiae). The bleeding tendency is due to decreased number of circulating platelets (thrombocytopenia). There is production of antibodies against the platelets by the patientâ€™s immune system. This case report was conducted to introduce the effectiveness of freshly donated blood and steroids on patients with immune thrombocytopenic purpura (ITP) after ingestion of herbal drugs.Case descriptionDT was a 30-year old female who presented with bleeding per vagina, gum bleeding and weakness. The patient did not have any systemic disease that would cause any spontaneous hemorrhage. The patient was referred to a hematologist urgently and her thrombocyte count was found to be 2000/Ã¬L. Other test results were in normal range. Full blood count revealed severe thrombocytopenia. Freshly donated whole blood was given to the patient and then the changes in her general condition were analyzed, as well as the blood test results.ConclusionIn the absence of platelet concentrate especially in rural settings and resource-poor countries, freshly donated whole blood can be used in the management of a case of severe thrombocytopenia from ITP.